Characterization of Patients with Ankylosing Spondylitis Receiving Secukinumab and Reasons for Initiating Treatment: A US Physician Survey and Retrospective Medical Chart Review - Reeti Joshi; Dominick Latremouille-Viau; Mark K. Meiselbach; Jipan Xie; Yujin Park; Prashanth Sunkureddi (Adis, Springer Healthcare, 2019)
Abstract Objectives To characterize US patients with ankylosing spondylitis (AS) who were treated with secukinumab and to assess rheumatologist-reported reasons for prescribing treatment in clinical practice. Methods This descriptive analysis of data from a US retrospective medical chart review included patients aged ≥ 18 years diagnosed with AS who initiated secukinumab after 15 January 2016. Eligible rheumatologists used online forms to collect patient demographics, disease characteristics, co-morbidity profile, and treatment history prior to or on the index date, defined as the date of the first secukinumab prescription recorded in the medical chart. Information on physician-level characteristics and reasons for secukinumab prescription and dosing were also collected. Results Medical charts from 78 patients with AS who initiated secukinumab were reviewed by 25 rheumatologists between 7 July 2017 and 11 August 2017. Overall, 76.9% of patients were male, mean (SD) age was 39.8 (10.8) years, and 34.6% were biologic naïve. The most common reasons for secukinumab initiation among biologic-naïve and biologic-experienced patients, respectively, were efficacy/effectiveness (77.8%) and failure of other prior biologics (84.3%). Nearly all patients (94.9%) received a loading dose, including 150 mg every week (39.7%), 300 mg every week (53.8%), and other (1.3%). Overall, 73 patients (93.6%) received ≥ 1 maintenance secukinumab dose, of whom 56.2% and 43.8% received 150 mg and 300 mg, respectively, every 4 weeks. Conclusions In this US medical chart review of patients with AS who initiated secukinumab, approximately one-third were biologic naïve, and secukinumab efficacy/effectiveness and failure of other biologics were the most common reasons for initiating secukinumab.